Hydrogenation/Deoxygenation (H/D) Reaction of Furfural-Acetone Condensation Product using Ni/Al2O3-ZrO2 Catalyst - Adam Mahfud; Siti Mariyah Ulfa; Edi Priyo Utomo (The Journal of Pure and Applied Chemistry Research, 2016)
The catalytic hydrogenation/deoxygenation (H/D) reaction was carried out using Ni/Al2O3-ZrO2 catalyst. The 10% (wt/wt) of Ni were impregnated on Al2O3-ZrO2 (10NiAZ) by wet impregnation method followed by calcination and reduction. X-Ray diffraction analysis showed that Nideposited on the surface, with specific surface areas (SBET) was 48.616 m2/g. Catalyst performance were evaluated for H/D reaction over furfural-acetone condensation products, mixture of 2-(4-furyl)-3-buten-2-on and 1,5-bis-(furan-2-yl)-pentan-3-one. The reaction was carried out in a batch, performed at 150°C for 8 hours. The H/D reaction gave alkane derivatives C8 and C10 by hydrogenation process followed by ring opening of furan in 15.2% yield. While, oxygenated product C10-C13 were also detected in 17.2% yield. The increasing of pore volume of 10NiAZ might enhance catalyst activity over H/D reaction. The alkene C=C bond was easy to hydrogenated under this condition by the lower bond energy gap.